Konsep Pertanggungjawaban Pidana pada Korporasi dalam Kasus Tata Kelola Minyak Mentah dan Produk Kilang PT. Pertamina : Dalam Perspektif Pasal 2 UU Tipikor - Mohammad Arqon; Fitri Handayani; Nessie Gusriyani; Fuji Cantika; Bunga Meisy Astrisia; Elsa Sapitri; Siti Alisa; Rona Roveria (Adagium: Jurnal Ilmiah Hukum, 2026)
Corporate sentencing in corruption crimes in Indonesia continues to encounter both normative and implementation barriers, particularly in imposing criminal liability on state-owned enterprises such as PT Pertamina (Persero). This study aims to examine the normative weaknesses of Article 2 of the Anti-Corruption Law and assess the scope of corporate criminal liability in the context of crude oil and refinery product governance. The research employs a normative juridical method through a statutory approach, conceptual approach, and case approach to interpret relevant legal norms without relying on empirical data. The findings indicate that although corporations have been formally recognized as subjects of criminal law, the legal framework governing corporate mens rea and the standards for proving organizational fault remain insufficiently defined. The absence of clear obligations regarding internal control systems and compliance programs within state-owned enterprises further increases the risk of governance irregularities. This study proposes a normative reconstruction through strengthening the concept of corporate mens rea, establishing binding compliance standards, and clarifying corporate sentencing mechanisms within the Anti-Corruption Law. These reforms are essential for enhancing the effectiveness of corruption eradication and safeguarding state financial interests.